2010
DOI: 10.1182/blood-2009-06-225375
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cyclophosphamide for severe aplastic anemia: long-term follow-up

Abstract: Severe aplastic anemia (SAA) is a lifethreatening bone marrow failure disorder that can be treated with bone marrow transplantation, immunosuppressive therapy, and high-dose cyclophosphamide. Here, we report long-term follow-up on 67 SAA patients (44 treatment-naive and 23 refractory) treated with high-dose cyclophosphamide. At 10 years, the overall actuarial survival was 88%, the response rate was 71% with the majority being complete, and the actuarial event-free survival was 58% in 44 treatmentnaive SAA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 36 publications
0
84
1
2
Order By: Relevance
“…1 Some might argue that treatment success in selected cases of syngeneic transplant is, in fact, not due to the transplant but is only the result of the immunosuppressive conditioning and posttransplant immunosuppression; as we know, treatment of AA with high-dose cyclophosphamide has been a topic of debate in the past. 17,18 Though the inability to measure donor chimerism precludes proof of syngeneic engraftment, rapid neutrophil recovery, as well as lack of influence of ATG, are strong surrogate indicators of actual engraftment rather than response to immunosuppressive treatment, which usually occurs after several months. 3 Despite the widespread use of ATG, its role in pre-transplant conditioning is also not clear in the setting of matched sibling transplant, where a randomized study failed to confirm the positive effect on engraftment observed in a retrospective comparison.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some might argue that treatment success in selected cases of syngeneic transplant is, in fact, not due to the transplant but is only the result of the immunosuppressive conditioning and posttransplant immunosuppression; as we know, treatment of AA with high-dose cyclophosphamide has been a topic of debate in the past. 17,18 Though the inability to measure donor chimerism precludes proof of syngeneic engraftment, rapid neutrophil recovery, as well as lack of influence of ATG, are strong surrogate indicators of actual engraftment rather than response to immunosuppressive treatment, which usually occurs after several months. 3 Despite the widespread use of ATG, its role in pre-transplant conditioning is also not clear in the setting of matched sibling transplant, where a randomized study failed to confirm the positive effect on engraftment observed in a retrospective comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological responses to transfusion independence appear in ~2/3 of patients; however, disease relapse ultimately occurs in 30-40% of patients (1,4). A 10-year follow-up study revealed that the response rate of SAA is 71% and the actual event-free survival is 58% in 44 treatment-naïve patients with SAA that received high-dose cyclophosphamide (15). The success of IST application is significantly limited by poor response, high relapse and clonal evolution.…”
Section: Discussionmentioning
confidence: 99%
“…After this promising pilot study, a phase 3 prospective trial to compare response rates to IST with either high-dose CY/CsA or ATG/CsA in treatment-naïve patients with SAA was conducted, which is terminated prematurely because of excessive early mortality related to fatal infectious complications followed by delayed neutrophil recovery of the CY/CsA arm [41]. However, a recently published long-term follow-up report of 67 SAA patients (44 treatment-naïve and 23 refractory) who were treated with high-dose CY (50 mg/kg for 4 consecutive days) showed acceptable response rates of 70.5 % (including CR of 43.2 %) and 47.8 % (including CR of 21.7 %), while the actual OS at 10 years was 88 and 61.8 % in treatment-naïve and refractory patients, respectively [46]. Early mortality rate was acceptable (7.5 %), but the cumulative incidence of fungal infections in the early post-treatment period at 2 months was 21 % in treatment-naïve and 39 % in refractory patients.…”
Section: Alternative Immunosuppressive Regimensmentioning
confidence: 99%
“…A third course of ATG-containing IST showed benefit only in previous responders, but not in patients who were refractory to previous IST [40]. On the other hand, cyclophosphamide (CY) or alemtuzumab is used as alternative IST regimen in these patients [41][42][43][44][45][46].…”
Section: Management Of Patients Who Have Refractory or Relapsed Aplasmentioning
confidence: 99%